Organosulfur Compounds in Nature - Sotheeswaran,S; Arambewela,Lakshmi (Colombo Institiute of Chemistry Ceylon, 2014)
Formation of 1- propenesulfenic acid from it precursor in onions
Keywords: compound,nature